Estresse, ansiedade, confiança e bem-estar do servidor público universitário em momento de pandemia Covid-19 - Menegazzi, Raquel Boff (2023)
Employee trust in the organization is a determining factor for a healthy and promising work environment; However, external factors can influence these issues, as in the case of the COVID19 pandemic, which affected the course of life on a global scale, negatively impacting physical health, social, psychological and economic aspects of society, including work environments. Thus, this research was motivated by the objective of analyzing the level of stress, anxiety, well-being at work and confidence of civil servants at the Federal University of Santa Maria/RS, in the face of the COVID-19 pandemic. To this end, an exploratory and descriptive research was carried out, of a quantitative nature, achieved through a field study (survey). The instrument used for data collection consisted of questions referring to the characterization of the profile of the participants and questions related to the research instruments, namely: Generalized Anxiety Disorder (GAD 7), by Bártalo, Monteiro and Pereira (2017); Stress Scale at Work (EET), by Paschoal and Tamayo (2004); Employee Confidence Scale in the Organization – ECEO, adapted from Oliveira and Tamayo (2008); and Workplace Wellbeing Scale (IBET-13), adapted from Siqueira, Orengo and Peiró (2014). Data analysis was performed using partial least squares structural equation modeling (PLS-SEM). For model evaluation, confirmatory factor analysis and evaluation of reliability criteria, convergent and discriminant validity were performed. A total of 375 responses were obtained, and with regard to the general characterization of the sample profile, it was predominantly made up of females (64.00%), aged between 31 and 40 years (30.13%), with married marital status( a) (62.14%), education at a specialization level (39.46%), with 11 to 20 years of service at the institution (32.53%). Through the analyses, it was possible to perceive that the evaluated constructs are influenced by sociodemographic variables, highlighting that severe anxiety is related to divorced civil servants, while moderate anxiety and moderate stress are related to the female gender. The proposed measurement model to measure the well-being of servers and its relationship with anxiety and stress at work was statistically validated. The assessments regarding the reliability and validity of the proposed statistical model met the requirements, making it empirically suitable for measuring the relationship between well-being and anxiety and stress at work. The results suggest that the servers' well-being dimension positively influences the reduction of anxiety and is positively related to the reduction of stress.